Chebyshev Wavelets Method for Solving Partial Differential Equations of Fractional Order - Mohammed, Osama H; Ameen, Haneen A (Al-Nahrain Journal of Science, 2018)
In this paper, we use the second kind Chebyshev wavelet operational matrix of fractional integration for solving fractional order linear partial differential equations.By using this method the fractional order partial differential equation is translated into Lyapunov type matrix equation and the computation effort become convenient. Two illustrative examples are provided to demonstrate the validity, simplicity and applicability of the numerical scheme based on the Chebyshev set of functions.